Twórczość publicystyczna Izabeli Moszczeńskiej - Pogracka-Michalak, Izabela (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
There are no well-known Polish female journalists or novelists from before the middle of the 19th century. This does not mean that they did not exist, but that they have been forgotten. The first Polish women writer was Gertruda, daughter of Mieszko II and Rycheza, who wrote in the 11th century. The first Polish woman author well known during her lifetime was Elżbieta Drużbacka née Kowalska (18th century). The breakthrough moment for women writers was positivism, when Eliza Orzeszkowa, Maria Konopnicka, Maria Rodziewiczówna, and Gabriela Zapolska all wrote. The Young Poland movement brought us many interesting articles, essays, and manifestos authored by females, but most of them existed only as first editions and are now almost inaccessible to readers. A particularly interesting woman was Izabela Moszczeńska, a writer, journalist, educationist, translator and feminist activist. Moszczeńska was the founder of the League of Polish Women and contributed to voting rights for women. Her literary and journalistic works are still timely and are a perfect starting point for modern feminist research.